Anti Chlamydial Antibodies in Women with Ectopic Pregnancy - Hina Bokhari , Imtenan Shahid , Farhan Rasheed , Abbas Hayat, Hina Bokhari , Imtenan Shahid , Farhan Rasheed , Abbas Hayat (Journal of Rawalpindi Medical College, 2017)
Background: To compare the frequency of chlamydia trachomatis infection in women with ectopic and with normal pregnancies. Methods: In this case-control study diagnosed patients of ectopic pregnancy(EP)were included . The control group comprised of early normal intra uterine pregnancies (1st trimester). A total number of 88, comprising 44 cases and 44 controls were included in this study. Sera from patients was drawn at the time of operation or within the subsequent 24 hours. Anti-chlamydial IgG was performed by ELISA. Results: Sampled cases population (n=44) had mean age distribution 26.48 years while among controls, mean age was 25.32 years. Presenting symptoms of cases showed pelvic pain (54.5%), bleeding (27.3%), vomiting (11.4%) and burning micturition (6.8%). During contraceptive practices , out of 88 patients, 5 cases and 20 controls gave history of safe sex practices. Out of 63 patients, who did not give history of any contraceptive practice, Anti-Chlamydia IgG was detected in 11 cases and 5 controls. Regarding Anti-Chlamydia IgG distribution among cases and controls, IgG was detected in 11(25%) cases and in 5(11.3%) controls. Conclusion: Frequency of anti-chlamydial IgG antibodies was much higher in women with ectopic pregnancy (25%) as compared to healthy controls(11.3%).